Pelatihan Budidaya Lebah Klanceng sebagai Motivasi Bisnis Kepada Santri Pondok Pesantren - Muhammad Fitri Budi Utomo; Siti Dinar Rezki Ramadhani Dinar; Sri Purwati (Universitas Veteran Bangun Nusantara, 2025)
Stingless bee (Trigona sp.) farming training serves as a practical and contextual strategy to foster entrepreneurial spirit among students in Islamic boarding schools. This activity was carried out at Oemah Jampi for the students of Isy Karima Islamic Boarding School with the aim of providing technical understanding of stingless bee (Trigona) farming and fostering business motivation based on local potential. The training encompassed educational sessions, hands-on technical workshops, practical field activities, and evaluations through pre- and post-tests. Results indicated a significant increase in participants' understanding, with average scores rising from 48.3 to 84.6. Additionally, students proposed simple business ideas, such as producing packaged honey and developing derivative products. The enthusiastic response from participants and the conducive environment of the boarding school suggest that stingless bee farming holds substantial promise as a medium for practical entrepreneurship education. This training not only transferred technical skills but also successfully instilled a sense of economic independence aligned with the boarding school's character. Similar training models have the potential to be replicated in other Islamic boarding schools as part of developing students' creative economies. Keywords: Stingless Bee Farming, Islamic Bboarding School, Training, Business